Triple ectopic thyroid: A rare entity - Nilegaonkar, Sujit (Medknow Publications & Media Pvt Ltd, 2011)
Ectopic thyroid tissue is an uncommon congenital aberration. It is extremely rare to have three ectopic foci at three different sites. The thyroid scan has been used successfully to diagnose ectopic thyroid tissue. We report a case of ectopic thyroid tissue at base of tongue, another at the level of hyoid and third one as aberrant tissue at suprahyoid location in a 16 year old female who presented with swelling in front of neck. This patient was clinically diagnosed as thyroglossal cyst and was being planned for surgery. Preoperative thyroid scan helped in establishing diagnosis of ectopic thyroid which was the only functioning thyroid tissue. Thus, it prevented unnecessary surgery. Therefore it is suggested that thyroid scan and USG/CT scan must be done as routine work up in neck swellings pre operatively to avoid unnecessary surgeries.